NK-cell responses are biased towards CD16-mediated effector functions in chronic hepatitis B virus infection - Schuch, Anita; Correia, Margareta; Cerwenka, Adelheid (Journal of hepatology, 2019)
Background & Aims - Phenotypic and functional natural killer (NK)-cell alterations are well described in chronic hepatitis B virus (cHBV) infection. However, it is largely unknown whether these alterations result from general effects on the overall NK-cell population or the emergence of distinct NK-cell subsets. Human cytomegalovirus (HCMV) is common in cHBV and is associated with the emergence of memory-like NK cells. We aimed to assess the impact of these cells on cHBV infection. - Methods - To assess the impact of memory-like NK cells on phenotypic and functional alterations in cHBV infection, we performed in-depth analyses of circulating NK cells in 52 patients with cHBV, 45 with chronic hepatitis C virus infection and 50 healthy donors, with respect to their HCMV serostatus. - Results - In patients with cHBV/HCMV+, FcεRIγ- memory-like NK cells were present in higher frequencies and with higher prevalence than in healthy donors with HCMV+. This pronounced HCMV-associated memory-like NK-cell expansion could be identified as key determinant of the NK-cell response in cHBV infection. Furthermore, we observed that memory-like NK cells consist of epigenetically distinct subsets and exhibit key metabolic characteristics of long-living cells. Despite ongoing chronic infection, the phenotype of memory-like NK cells was conserved in patients with cHBV/HCMV+. Functional characteristics of memory-like NK cells also remained largely unaffected by cHBV infection with the exception of an increased degranulation capacity in response to CD16 stimulation that was, however, detectable in both memory-like and conventional NK cells. - Conclusions - The emergence of HCMV-associated memory-like NK cells shapes the overall NK-cell response in cHBV infection and contributes to a general shift towards CD16-mediated effector functions. Therefore, HCMV coinfection needs to be considered in the design of immunotherapeutic approaches that target NK cells in cHBV. - Lay summary - In chronic hepatitis B virus infection, natural killer (NK)-cell phenotype and function is altered. In this study, we demonstrate that these changes are linked to the emergence of a distinct NK-cell subset, namely memory-like NK cells. The emergence of these memory-like NK cells is associated with coinfection of human cytomegalovirus that affects the majority of patients with chronic hepatitis B.
Laut Frontdoor: Anita Schuch, Britta Franziska Zecher, Philipp Andreas Müller, Margareta P. Correia, Franziska Daul, Charlotte Rennert, Catrin Tauber, Karolin Schlitt, Tobias Boettler, Christoph Neumann-Haefelin, Hartmut Hengel, Hanspeter Pircher, Adelheid Cerwenka, Robert Thimme, Maike Hofmann
Available online 18 October 2018
Gesehen am 06.09.2019